2018
DOI: 10.1016/j.devcel.2018.01.010
|View full text |Cite|
|
Sign up to set email alerts
|

The Polyploid State Plays a Tumor-Suppressive Role in the Liver

Abstract: Most cells in the liver are polyploid, but the functional role of polyploidy is unknown. Polyploidization occurs through cytokinesis failure and endoreduplication around the time of weaning. To interrogate polyploidy while avoiding irreversible manipulations of essential cell-cycle genes, we developed orthogonal mouse models to transiently and potently alter liver ploidy. Premature weaning, as well as knockdown of E2f8 or Anln, allowed us to toggle between diploid and polyploid states. While there was no detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
159
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 146 publications
(170 citation statements)
references
References 65 publications
10
159
0
1
Order By: Relevance
“…E). Together, these data are consistent with other reports and show that LKO mice are highly susceptible to DEN/PB‐mediated tumorigenesis, suggesting that the hepatic polyploid state protects the liver from tumor formation.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…E). Together, these data are consistent with other reports and show that LKO mice are highly susceptible to DEN/PB‐mediated tumorigenesis, suggesting that the hepatic polyploid state protects the liver from tumor formation.…”
Section: Resultssupporting
confidence: 93%
“…LKO mice are enriched with the most proliferative cells (diploids), and, upon tumor initiation, the large numbers of rapidly cycling diploid hepatocytes in LKO mice drive tumorigenesis. A third mechanism was recently described by Zhang et al, where they showed that polyploid hepatocytes protect from liver cancer . In a series of elegant experiments, polyploid hepatocytes were found to “buffer” against loss of tumor suppressors.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…At least in yeast, polyploidization (tetraploidization) can induce beneficial mutations leading to environmental adaptation . A recent report suggested that tetraploidy in hepatocytes is rather tumor‐suppressive, indicating a complex relationship between tetraploidy and cancer.…”
Section: Tetraploidy‐induced Tissue Disorders and Cancermentioning
confidence: 99%